Does Economic Growth, Wage Rate, and Industrial Development Matter for Labor Absorption? - Dirta Pratama Atiyatna; Ichsan Hamidi; Trie Sartika Pratiwi; Hamira Hamira (Jurnal Ekonomi Pembangunan, 2023)
The dimensions of employment problems are not just limited field or job opportunities and low productivity but are much more serious with different causes. This study aims to determine the effect of the rate of economic growth, economic growth, minimum wages, and the number of industrial units on employment in South Sumatra Province. The data analysis method used in this study is a quantitative analysis method using panel data regression and usage. This research covers a broad scope, namely as many as 17 districts/cities in South Sumatra for 6 years (2014-2019). Based on the results of the analysis and discussion that has been carried out, it can be concluded that the districts/cities in South Sumatra Province in 2016-2019 had the highest employment by looking at the Random Effect Model (REM) labor estimation coefficient which shows that the highest employment is in Palembang City at 75,452,015. Meanwhile, the lowest value is in the Ogan Ilir district at 68,194,663.